Hubungan di antara gaya komunikasi guru besar dengan komitmen guru sekolah rendah di Daerah Sandakan, Sabah - Maslinah, Mohd. Taib (2011)
The purpose of the study was to identify the relationship between the communication styles of head masters and commitment of primary school teachers in the District of Sandakan. The aspects being studied were 10 communication styles namely Friendly, Impression Learning, Relaxed, Animated, Attentiveness, Contentions, Expressive, Dramatic, Open and Dominant while three types of commitment were Identification, Involvement, and Loyalty. The research sample consisted of 148 school teachers who were randomly selected from 5 primary urban schools. The studied had used questionnaire approach to collect the research data. The instrument Communicator Style Measure (CSM) by Norton (1983) was employed to measure the abovementioned dimensions. The Alpha Cronbach value for the communication styles were reported .95. The instrument used for Organizational Commitment was developed by Cook (1980) which had Alpha Cronbach value of .89 in this study. The questionnaires were collected, reviewed and analyzed by using Statistical Package for Social Sciences (SPSS) version 19.0 through means, frequencies, percentages, and standard deviations. To test the 10 hypothesis developed for the study, the correlation coefficients of Pearson,r were used. The findings had shown that 9 dimensions of communication styles were significantly related with teacher commitment and while Animated dimension was not significantly related with teacher commitment. Some recommendations for improvement were made such as to extend the scope of study to other districts in Sabah especially in the rural areas involving larger samples.